If it bleeds, it leads: the construction of workplace injury in Canadian newspapers, 2009–2014. (September 2015) - Barnetson, Bob; Foster, Jason
Abstract : Background: Public perceptions of workplace injuries are shaped by media reports, but the accuracy of such reports is unknown. Objectives: This study identifies differences between workers' compensation claims data and newspaper reports of workplace injuries in Canadian newspapers and media sources. Methods: This study applies quantitative content analysis to 245 Canadian English-language newspaper articles from 2009 to 2014. Workers' compensation claims data is drawn from the Association of Workers' Compensation Boards of Canada. Results: Newspapers dramatically overreport fatalities, injuries to men, injuries in the construction and mining/quarrying/oil industries, injuries stemming from contact with objects/equipment and fires/explosions, and acute physical injuries such as burns, fractures, intracranial injuries, and traumatic injuries. Newspaper reporters tend to rely upon government, police/firefighter, and employer accounts, rarely recounting the perspectives of workers. Conclusion: Newspapers overreported fatalities, injuries to men, and injuries in the construction and mining/quarrying/oil industries. This results in a misleading picture of occupational injuries in Canada.